Servir le roi autour de 1300 - Philippe Josserand (Medievalista)
Guillaume de Nogaret was keeper of the seal and master of Capetian politics at the beginning of the fourteenth century. Expert jurist and administrator, he was one of the very first servants of the royal State whose entire sovereignty, against the papacy in particular, he wanted to assert to the point of making it a true mystic. However, the man, who suffers from a dark legend, is little known. Recent investigations, largely unpublished, have focused on his practice of power, but no biography has been dedicated to him from the end of the nineteenth century. The article, of course, does not claim to fill such a gap. Yet, it illustrates the possibility of a biographical seizure, the interest which would be that of such a research, and, beyond the myth, by linking the action of Guillaume de Nogaret in the French South and to the Capetian court, it reveals the main lines of an existence entirely dedicated to royal service and carried, to the point of brutality, by the obsession with the interest of the realm erected, in deeds and in thought, into a mystic then completely new, opening the way to the absolutism.